Prevalence of Amblyopia among School age children in Eye University Hospital, Kabul – Afghanistan - Jawhar, Mohammad Sadeq; Tawhid, Mohammad Homayun; Khurasani, Mohammad Haroon; Anwar, Idris; Rahimi, Hashmatullah Mawlana; Pirzad, Ahmad Fawad (Eximia, 2023)
Introduction: Amblyopia is the reduction of monocular and rarely binocular vision, in the best case, it is the correction of the refractive error, which is caused by the visual deprivation of the affected eye or the abnormality of the binocular interaction, which does not have any other pathology in the way of vision. Amblyopia occurs in the most fundamental period of the development of visual system. It is estimated that the age of occurrence is between 0-8 years old and its prevalence is between 0.2-6.2 % globally. Objective: Amblyopia is one of the worrying problems among children in Afghanistan, and epidemiological studies are considered necessary for its management. On this occasion, an attempt has been made to explain the prevalence of amblyopia in school age children, according to their age, gender and correspondence. Method and Data collection: This is a retrospective cross-sectional (descriptive) study and all the information of 2151 patients were obtained from the files of patients in the age group of 7-18 years' old who were visited by the eye University hospital from 21 March to 22 Sep 2022. Then those patients who have been diagnosed with amblyopia; have been studied. Results: Out of 2151 participants aged 7-18 years with various eye complaints, 152 of them (7%) have amblyopia. 7.9% (89 Participants) are boys and 6.09 % (63 Participants) are girls. Unilateral amblyopia is found in 74.34% of cases (113 Participants) and bilateral amblyopia in 25.65% of cases (39 Participants). Conclusion: 7% of school age children, average age of 13.39 years is suffering from amblyopia. Percentage of amblyopia is higher in boys than in girls and; most patients have unilateral amblyopia.